2022
DOI: 10.2196/36809
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of a Social Media–Based Intervention (Run4Love) on Depressive Symptoms of People Living With HIV: 3-Year Follow-up of a Randomized Controlled Trial

Abstract: Background Emerging studies have shown the effectiveness of mobile health (mHealth) interventions in reducing depressive symptoms among people living with HIV. Most of these studies included only short-term follow-up, with limited data on long-term effects. Objective The purpose of this study is to assess the long-term effects of a randomized controlled trial called Run4Love on depressive symptoms among people living with HIV at 1-year and 3-year follow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…A total of 11 themes and 2 individual observations were identified by the reviewers for a total of 48 occurrences in the literature, whereas 11 themes and 7 observations were noted for a total of 95 observations. In the 33 studies analyzed, 26 (79%) showed an improvement in symptoms of depression [25,26,[28][29][30][31][32][33][35][36][37][40][41][42][43][44][46][47][48][49][50][51][52][54][55][56], while 19 (58%) showed an improvement in anxiety [26][27][28][29][30][31][32][33]36,[38][39][40][44][45][46][53][54][55][56]. Only 11/33 (33%) reported that at least one symptom was not statistically significant when compared with results from the control group, but the improvement was still noted [25]…”
Section: Results Of Interventions Compared With the Control Groupsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 11 themes and 2 individual observations were identified by the reviewers for a total of 48 occurrences in the literature, whereas 11 themes and 7 observations were noted for a total of 95 observations. In the 33 studies analyzed, 26 (79%) showed an improvement in symptoms of depression [25,26,[28][29][30][31][32][33][35][36][37][40][41][42][43][44][46][47][48][49][50][51][52][54][55][56], while 19 (58%) showed an improvement in anxiety [26][27][28][29][30][31][32][33]36,[38][39][40][44][45][46][53][54][55][56]. Only 11/33 (33%) reported that at least one symptom was not statistically significant when compared with results from the control group, but the improvement was still noted [25]…”
Section: Results Of Interventions Compared With the Control Groupsmentioning
confidence: 99%
“…The following observations only occurred once in the literature: decrease in anger [26], decrease in decision conflict [30], decrease in decision regret [30], decreased digestive disturbance [26], decreased pain [26], increased medication adherence [41], and the intervention had no effect on self-efficacy [34]. [25,26,[28][29][30][31][32][33][35][36][37][40][41][42][43][44][46][47][48][49][50][51][52][54][55][56] 19 Reduced anxiety [26][27][28][29][30][31][32][33]36,[38][39][40][44][45][46][53]…”
Section: Results Of Interventions Compared With the Control Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…They all use Chinese questionnaires that have been validated for the evaluation of Chinese patients. [22][23][24] The MoCA tests eight major neurocognitive domains, including short-term memory recall (no score), visuospatial ability, naming, attention, language, conceptual thinking, working memory, and orientation of time and place. The MoCA, with a sensitivity of 90% and a specificity of 87%, 25 is used to identify patients with mild cognitive impairment.…”
Section: Definition Of Cognitive Impairmentmentioning
confidence: 99%